2015
DOI: 10.1038/labinvest.2015.104
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and pharmacologic targeting of EZH2, a fetal retinal protein and epigenetic regulator, in human retinoblastoma

Abstract: Retinoblastoma (RB) is the most common primary intraocular cancer in children, a nd the third most common cancer overall in infants. No molecular-targeted therapy for this lethal tumor exists. Since the tumor suppressor RB1, whose genetic inactivation underlies RB, is upstream of the epigenetic regulator EZH2, a pharmacologic target for many solid tumors, we reasoned that EZH2 might regulate human RB tumorigenesis. Histologic and immunohistochemical analyses were performed using an EZH2 antibody in sections fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 53 publications
(72 reference statements)
1
21
0
1
Order By: Relevance
“…Among the two HMTs that regulate H3K27 trimethylation, Ezh1 and Ezh2 , and the demethylase Jmjd3 , Ezh2 and Jmjd3 are widely expressed in retinal progenitors during development; Ezh1 is expressed only weakly in the postnatal retina 29 . The transient expression of Ezh2 during development, which is completely repressed postnatally in the retina, was also confirmed during human retinal development 11 . A cell type specific effect was also observed with Jmjd3 deficiency, which resulted in impaired differentiation of subsets of bipolar cells, despite strong Jmjd3 expression in the RGCs 9 .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Among the two HMTs that regulate H3K27 trimethylation, Ezh1 and Ezh2 , and the demethylase Jmjd3 , Ezh2 and Jmjd3 are widely expressed in retinal progenitors during development; Ezh1 is expressed only weakly in the postnatal retina 29 . The transient expression of Ezh2 during development, which is completely repressed postnatally in the retina, was also confirmed during human retinal development 11 . A cell type specific effect was also observed with Jmjd3 deficiency, which resulted in impaired differentiation of subsets of bipolar cells, despite strong Jmjd3 expression in the RGCs 9 .…”
Section: Discussionmentioning
confidence: 56%
“…Ezh2 trimethylates histone H3 at lysine 27 (H3K27me3), a repressive histone mark that is known to persist into adulthood 7 8 . Previous reports have shown that Ezh2 / EZH2 is abundant during embryonic development but is absent during the late postnatal period and adulthood in mice and humans 9 10 11 . Conditional loss-of-function experiments in which an early (E9.5) retinal Cre driver, such as Dkk3 - 12 or Pax6-αCre , was used to delete retinal Ezh2, has demonstrated a role for this HMT in the proliferation and differentiation of retinal progenitor cells (RPCs) 13 14 .…”
mentioning
confidence: 94%
“…The above in vitro models are complemented by classical xenograft or orthotopic murine tumor models with established human or syngeneic murine cancer cell lines, genetically engineered murine tumor models, or patient-derived xenograft tumors grown in immunodeficient mice [173,174,175,176,177,178,179,180,181,182,183,184].…”
Section: Current Preclinical Models To Assess Cellular Radiation Rmentioning
confidence: 99%
“…21 Several studies conducted with solid tumor cell lines have suggested that GSK126 suppresses cell migration and angiogenesis, but has a limited therapeutic effect when used alone. [22][23][24] Therefore, we hypothesized that a combination of GSK126 and diosgenin might be more potent for attenuating GC metastasis when compared to using GSK126 or diosgenin alone.…”
Section: Introductionmentioning
confidence: 99%